2014
DOI: 10.1021/jp502411u
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Mixed-Stack Organic Charge-Transfer Crystals

Abstract: The electronic structures of a series of donor− acceptor mixed-stack crystals have been investigated by means of density functional theory calculations. The results highlight that a number of the donor−acceptor crystals under consideration are characterized by wide valence and conduction bands, large hole and electron electronic couplings, and as a result very low hole and electron effective masses. The fact that the effective masses and electronic couplings for holes and electrons are nearly equal along the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
95
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 41 publications
4
95
2
Order By: Relevance
“…Unlike in the previously studied donor-acceptor systems [2,7], the frontier orbitals of the complex do not describe a complete charge-transfer and have localized character mixed-in (Figure 3). As a result, obtained energy gap is higher than the energy gap (2.36 eV) calculated from the electrochemical measurements of the oxidation potential of DTT (1) i For triphenylene, see [28], and the larger aromatic hydrocarbons, see [43].…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…Unlike in the previously studied donor-acceptor systems [2,7], the frontier orbitals of the complex do not describe a complete charge-transfer and have localized character mixed-in (Figure 3). As a result, obtained energy gap is higher than the energy gap (2.36 eV) calculated from the electrochemical measurements of the oxidation potential of DTT (1) i For triphenylene, see [28], and the larger aromatic hydrocarbons, see [43].…”
contrasting
confidence: 59%
“…No charge-transfer bands were reported for ferrocene and nickelocene in co-crystals with macrocycle I [44]. comparable to the bandwidths found in anthracene-TCNQ and tetracene-TCNQ crystals [7]. As a result of such large band gaps and almost flat bands, charge transport in these co-crystals is not expected to be efficient; further modification of the electronic properties of the donor and/or acceptor is required.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Similar mechanisms have been discussed in the context of other systems, where disorder plays no role. For organic donoracceptor co-crystals it has been predicted that conduction and valence bands are formed by superexchange coupling between spatially separated acceptors (donors) bridged by the noncovalently linked donors (acceptors), leading to a mirror symmetry of conduction and valence bands with remarkably small effective masses of electrons and holes [8][9][10]. In this Letter, we demonstrate that coherent superexchange processes can also contribute significantly to charge carrier mobility of disordered organic semiconductors.…”
mentioning
confidence: 72%
“…[9][10][11][12][13][14] Although this value is much smaller than that of single component, it does not mean that the intrinsic charge transport of CT complexes is inferior. 16,17 Therefore, it is still a question whether the performance of FETs based on the CT complexes can overpass their monomer counterpart. 15 In addition, theoretical studies indicated that they do have remarkable ambipolar charge transport characteristics.…”
mentioning
confidence: 99%